The Privacy Risks of Direct-to-Consumer Genetic Testing: A Case Study of 23andMe and Ancestry - Samual A. Garner; Jiyeon Kim (Washington University Law Review, 2019)
Direct-to-consumer genetic testing (DTC-GT) companies have proliferated and expanded in recent years. Using biospecimens directly submitted by consumers, these companies sequence and analyze the individual’s genetic information to provide a wide range of services including information on health and ancestry without the guidance of a healthcare provider. Given the sensitive nature of genetic information, however, there are growing privacy concerns regarding DTC-GT company data practices. We conduct a rigorous analysis, both descriptive and normative, of the privacy policies and associated privacy risks and harms of the DTC-GT services of two major companies, 23andMe and Ancestry, and evaluate to what extent consumers’ genetic privacy is protected by the policies and practices of these two companies. Despite the exceptional nature of genetic information, the laws and agency regulation surrounding genetic privacy and DTC-GT services are fragmented and insufficient. In this analysis, we propose three categories of privacy harms specific to DTCGT—knowledge harms, autonomy and trust-based harms, and data misuse harms. Then, through the normative lens of exploitation, we argue that 23andMe and Ancestry’s data practices and privacy policies provide consumers with insufficient protection against these harms. Greater efforts from both the industry and legal system are necessary to protect DTC-GT consumers’ genetic privacy as we advance through the era of genomics and precision medicine.
Keywords: Genetic testing; Direct-to-consumer genetic testing; 23andMe; Ancestry; Genetic privacy; Consumer privacy; Data misuse; Data privacy